(untitled) (Journal of the College of Education for Women, 2019)
The childhood stage is considered the most important stage of all the stages throughthe human being’s life. In this stage the human being will be more affected by the variousfactors that surround him/her. The first five years of his/her life leave a great impact not onlyon the human being personality, but also on his/her whole life. Therefore, it is worthwhile tobe concerned with and focus at the raising up and the teaching of the child during thechildhood stage.The mission of raising up children in this era - the era of globalization and informationbursting or news flooding – has become a very difficult or even an impossible mission.Furthermore, not only in the Arabic world, but also all over the world, this era has become adepressing and a disappointing era to many serious parents and teachers, who seek the factand care about both their children’s benefit and the benefit of those who raise them up.Children are seen to be more accepting to and more connecting with the building up ofcivilization. The parent’s attentiveness and the level of their educational maturity will definethe level of family evolution and its role in affecting the child’s personality.Eventually, all these matters go back to the shortage in the environmental attentivenessand its relation to the health of the human beings. All these leads to the problem discussed inthis research which is the revealing of the attentiveness by the problem of technological mediapoisoning of the children’s parents and their teachers.The aim of this research is to be acquainted with: The attentiveness of the technological media poisoning in the members of the sample. The attentiveness of the technological media poisoning in the kindergarten teachers. The differences in the attentiveness of the technological media poisoning. between the kindergarten children’s parents and the children’s teacher.This research is limited the children’s parents and teachers of the kindergartens inBaghdad for the academic year 2012-2013.In order to achieve the goal of this research, the researcher has performed a scale of theattentiveness of the technological media poisoning according to the scientific steps in theconstruction of the psychological scales.To approve the truth of the scale to be introduced to a number of experts. Afterstraightening some of the scale items, (33) the of the scale has been approved.Moreover, the researcher uses statistical analysis for the items by calculating thedistinctive power, which proves that all the items of the scale are distinctive and statisticallysignificant. The researcher tries to find out the relation between the degree of the item and thetotal degree.The validity of the scale has been approved by repeating the test. The validity factor is(0.86), which proves that the validity factor is reliable. In the application of the Falkronbachformula, it has been found that the validity factor is (0.93). This proves that the validity factoris reliable.The scale has been applied on (600) members of the sample, whichcontains randomlychosen children’s parents and kindergarten teachers.The result of the research are as follows: All the members of the sample have attentiveness of the technological media poisoning. The children’s parents have attentiveness of the technological media poisoning. The kindergarten teachers have attentiveness of the technological media poisoning. There are differences in attentiveness between all the members of the sample to thebenefit of the mothers side.The researcher has introduced a number of recommendations and suggestions, whichare going to be discussed later.